Dairy Product Consumption and Oligo-Astheno-Teratozoospermia Risk: A Hospital-Based Case-Control Study in China - Wang, Xiao-Bin; Wu, Qi-Jun; Guo, Ren-Hao; Leng, Xu; Du, Qiang; Zhao, Yu-Hong; Pan, Bo-Chen (Frontiers in Nutrition, 2021)
Background: The association between dairy products consumption and Oligo-astheno-teratozoospermia (OAT) risk has been limited and controversial. Therefore, we aim to explore the aforementioned association among Chinese men. Methods: A hospital-based case-control study was conducted in men consisting of 106 cases of OAT and 581 controls. Dairy products and related nutrients intake were collected using a semi-quantitative food frequency questionnaire and semen quality were analyzed according to the World Health Organization guidelines. The daily intake of dairy products and related nutrients was categorized into three groups with the lowest tertile defined as the referent category. Odds ratios (ORs) and 95% confidence intervals (CIs) of association between dairy intake and OTA risk were calculated by the multivariable logistic regression models. Results: No significant association was found between total dairy (OR T3vs.T1 =1.53, 95%CI: 0.85-2.78), protein (OR T3vs.T1 =1.51, 95%CI: 0.84-2.75), or calcium (OR T3vs.T1 = 1.46, 95%CI: 0.81-2.66) and OAT risk in main findings. However, we observed a statistically significant positive association of dairy fat intake with OAT risk (OR T3vs.T1 =1.93, 95%CI: 1.06-3.58). The findings were consistent with the main results when we carried out subgroup analysis stratified by body mass index. Conclusion: A significant positive association was only found between dairy fat intake and the risk of OAT. Further prospective large-scale studies are required to confirm this finding.